Assessing changes of carbon stock in dipterocarp forest due to hydro-electric dam construction in Malaysia - Dullah H.; Malek M.A.; Omar H.; Mangi S.A.; Hanafiah M.M. (Springer Science and Business Media Deutschland GmbH, 2023)
angiosperm; carbon sequestration; carbon sink; dam construction; data acquisition; deforestation; environmental assessment; hydroelectric power plant; Landsat multispectral scanner; landscape ecology; remote sensing; satellite data; satellite imagery; support vector machine; Kenyir Lake; Malaysia; Terengganu; West Malaysia; carbon; carbon sequestration; environmental protection; forest; Malaysia; river; Carbon; Carbon Sequestration; Conservation of Natural Resources; Forests; Malaysia; Rivers